Photochemical addition of cyclic ethers/acetals to olefins using tBuOOtBu: Synthesis of masked ketones/aldehydes and diols. Issue 44 (30th October 2020) - Hayakawa, Mamiko; Shimizu, Rina; Omori, Hajime; Shirota, Hisashi; Uchida, Kou; Mashimo, Hiroshi; Xu, Han; Yamada, Ryuusei; Niino, Seiya; Wakame, Yoshiki; Liu, Chuanxiang; Aoyama, Tadashi; et al.
Abstract: A fast photochemical C–C bond formation between cyclic ethers/acetals and olefins using di- tert -butyl peroxide (DTBP) was developed. This method provides easy access to 2-substituted cyclic ethers, and 2- or 4-substituted cyclic acetals. Acyl/formyl groups or diols can be obtained by the hydrolysis of the 2- or 4-substituted cyclic acetals, respectively. The reactions proceeded at room temperature and gave the expected products in good to excellent yields; efficient reactions were completed within 0.5 h at room temperature in >95% yield. Graphical abstract: Image 1 Highlights: Photochemical addition of cyclic ethers/acetals to olefins proceeded efficiently. Efficient reactions are completed within 0.5 h at room temperature in > 95% yield. The reaction is a synthesis of masked ketones/aldehydes and diols.